Deriving an ontology for knowledge management in collaborative innovation networks - Barradas, Luís Cláudio (2018)
Innovation and knowledge creation are tightly related concepts. Collaborative innovation networks (COINs) are very productive ecosystems for knowledge generation. Acknowledging their relevance for innovation, we propose a novel ontology for knowledge management (KM) in COINs, which builds on COINs related literature and is partially derived from topic-related and enterprise ontologies. The utility of the ontology is illustrated through an application case in a software house. The ontology can be applied in different cases involving KM in COINs, such as support the development of IT-based KM services for knowledge co-creation in COINs or, be used as an auditing tool in collaborative innovation processes.